2006
DOI: 10.1016/j.cellbi.2005.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Role of the actin cytoskeleton during respiratory burst in chemoattractant‐stimulated neutrophils

Abstract: Running Title: The actin cytoskeleton and the respiratory burstThe actin cytoskeleton and the respiratory burst -Bengtsson et al. 2 ABSTRACTThe aim of this study was to clarify the role of the actin cytoskeleton during chemotactic peptide fMet-Leu-Phe (fMLF)-stimulated respiratory burst in human neutrophil granulocytes. Reactive oxygen species (ROS) was measured as luminol-amplified chemiluminescence (CL) and F-actin content as bodipy phallacidin fluorescence in neutrophils treated with latrunculin B or jaspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 49 publications
2
28
0
1
Order By: Relevance
“…Earlier studies have suggested that disruption of actin fibers at the plasma membrane and phagosomes enhances the fMLP-triggered oxidative burst in phagocytes (26). These observations are further supported in the present study of lung ECs by our demonstration that disruption or depolymerization of actin filaments by cytochalasin D or latrunculin A markedly increased basal and hyperoxia-mediated ROS production, whereas stabilization of actin filaments with phalloidin blocked the oxidative response.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Earlier studies have suggested that disruption of actin fibers at the plasma membrane and phagosomes enhances the fMLP-triggered oxidative burst in phagocytes (26). These observations are further supported in the present study of lung ECs by our demonstration that disruption or depolymerization of actin filaments by cytochalasin D or latrunculin A markedly increased basal and hyperoxia-mediated ROS production, whereas stabilization of actin filaments with phalloidin blocked the oxidative response.…”
Section: Discussionsupporting
confidence: 80%
“…Accumulating evidence supports a link between the actin cytoskeleton and actin-binding proteins in the activation of phagocytic and non-phagocytic NADPH oxidase (23)(24)(25)(26)(27). Stimulation of neutrophils with phorbol ester induces translocation of p47 phox to the cytoskeleton without altering the distribution of either p40 phox or p67 phox and increases the oxidase activity that co-sediments with a heavy plasma membrane fraction consisting of actin and fodrin (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, actin depolymerization was shown to promote p47 phox -dependent, Nox2-mediated superoxide production in neutrophils (65) and endothelial cells (66). The underlying mechanism is likely 2-fold as follows: actin depolymerization enhances receptorinduced signaling pathways leading to the assembly of Nox2 from cytosolic and membrane-bound components, and it may also remove physical constraints from the association of these.…”
Section: Discussionmentioning
confidence: 99%